Efficacy of Cevimeline on Xerostomia in Sjögren's Syndrome Patients: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Mehdi Karimi, MD; Fatemeh Ahmadi Hajikolaei, MD; Fahime Hoseinpour, MD; Seyed-Ali Hashemi, MD; Anita Fatehi, MD; Seyed-Abbas Pakmehr, MD; Niloofar Deravi, MD; Mahdyieh Naziri, MSc; Mohaddeseh Belbasi, MD; Sahar Khoshravesh, MD; Seyed Hossein Vaezzadeh, MD (Current Therapeutic Research)
Background: Xerostomia, or dry mouth, is a common and debilitating symptom in patients with Sjögren's syndrome, affecting their quality of life. Although Cevimeline, a muscarinic agonist, has been investigated as a potential treatment, its efficacy and optimal dosage remain uncertain. This study aims to assess the effectiveness of Cevimeline in relieving xerostomia in patients with Sjögren's syndrome by a meta-analysis of randomized clinical trials (RCT). Method: A comprehensive search was conducted across PubMed, Scopus, Cochrane, and Web of Science databases, utilizing Medical Subject Headings terms and keywords related to “cevimeline,” “xerostomia,” and “Sjögren's syndrome” from inception until January 3, 2024. Studies were selected based on predefined inclusion criteria, focusing on clinical trials involving human subjects treated with cevimeline for xerostomia in Sjögren's syndrome. Data extraction was performed systematically, and statistical analysis was conducted using STATA software. Result: This meta-analysis included three RCTs with a total of 302 patients with Sjögren's syndrome (Cevimeline = 187; Placebo = 115). The analysis demonstrated that Cevimeline significantly reduces xerostomia (regarded as salivary flow, mouth dryness) in patients with Sjögren's syndrome with a pooled odds ratio –5.79 (95% CI [–10.55, –1.03]; I2 = 39.6%). Conclusions: In summary, cevimeline significantly increases salivary flow secretion rates in patients with Sjögren's syndrome. With a favorable safety profile at recommended dosages, cevimeline represents a viable therapeutic option for managing xerostomia, particularly in patients with mild to moderate salivary gland destruction.